Penerapan Model Pembelajaran PBL untuk Mengembangkan Habits of Mind Mahasiswa - Asep Sujana (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2015)
This research is a mixed method research with concurrent embedded strategy. The aim of the research is to find out the students’ habit of mind who learn with Problem-Based Learning (PBL) is better than the conventional learning. The population of the research is the mathematical education students of FKIP of Banten Mathla’ul Anwar University (Unma). The sample of the research is two classes in semester IV. The instruments in this research area essay, questionnaires and observation sheet of students’ and lecturers activities. The data are analyzed quantitatively and qualitatively that obtained from the pretest and posttest. The results show that there is no significant difference between the students’ habit of mind who learnt with the problem-based learning (PBL) and the conventional learning.